PERILAKU KESELAMATAN DAN KESEHATAN KERJA MAHASISWA VOKASI KEPERAWATAN DI KOTA PALEMBANG - Pitri Noviadi (Politeknik Kesehatan Kementerian Kesehatan Banten, 2022)
Students are the prospective nurses who participate in providing services in health services, so that in addition they must provide Occupational Safety and Health (OSH) capabilities because of the high probability and health risks in health services, especially hospitals. This study aims to determine of the relationship between knowledge, attitudes and a characteristics with the OSH behavior of Vocational Nursing students in the Palembang City. The research design is an Analytical Survey with Cross Sectional approach. The sample amounted to 175 students from Nursing Study Program at Polytechnic of the Ministry of Health Palembang, STIKES Muhammadiyah Palembang, and STIKES Aisiyah Palembang. Research variables consist of age, gender, OSH courses that have been obtained, knowledge, attitudes and OSH behavior. This study found that the variable that determines student OSH behavior is gender (Exp B = 9.131). These results are male students have a risk of 9.131 times compared to women for poor OSH behavior controlled by the variables of age, knowledge and attitude. Overall, the variables that determine student OSH behavior are gender, age, knowledge and attitude. Suggestions in this research is the need to apply OSH program in vocational DIII Nursing. It is necessary to increase students' knowledge and attitudes through OSH training and seminars. For educators, they can further improve as a role model for the implementation of OSH. Based on this research, further research can be carried out by developing research methods, larger samples and implementing OSH in other parts of the campus environment.